2015
DOI: 10.7763/joebm.2015.v3.232
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Structure and Bank Performance

Abstract: Abstract-This paper provides evidence on the impact of different types of ownership structure on bank performance. Using secondary data, the empirical analysis of this study is confined to Malaysian commercial banks during the period of 2000 to 2011. Multiple regression with fixed effects model is used to test the research model. Testing on five categories of ownership structure such as insider, family, government, institutional and foreign ownership, the results suggest that bank performance varies with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 42 publications
2
31
2
4
Order By: Relevance
“…Institutional investors are prevalent in Oman and concerned with ROA as it appears in the MSM report (MSM companies Guide, 2017). However, this notion is consistent with that of Abdul Rahman and Md Reja (2015), who assumed that if investors have insufficient ownership percentage then it will not affect performance.…”
Section: Model 2 (Dependent Variable-roe)supporting
confidence: 84%
See 1 more Smart Citation
“…Institutional investors are prevalent in Oman and concerned with ROA as it appears in the MSM report (MSM companies Guide, 2017). However, this notion is consistent with that of Abdul Rahman and Md Reja (2015), who assumed that if investors have insufficient ownership percentage then it will not affect performance.…”
Section: Model 2 (Dependent Variable-roe)supporting
confidence: 84%
“…The final group of evidence pertains to empirical studies that found no relationships or impacts of ownership concentrations on firm performance. Few studies, such as Qin, Mishra and Smyth (2012) and Abdul Rahman and Md Reja (2015), concluded this result for certain reasons. For example, Abdul Rahman and Md Reja (2015) concluded that the model used in several studies does not explain the changes in firm performance owing to other factors, such as research sample, variables, period of study, or statistical data.…”
Section: Literature Review-no Associationmentioning
confidence: 98%
“…A study by Florackis and Ozkan (2009) finds that institutional ownership is not always concentrated enough to accumulate voting power to monitor management. Rahman and Reja (2015) find no association between institutional investors and bank performance. Piesse et al (2012) examine the ownership structure in listed firms of Saudi Arabia and Egypt and indicate that the role of institutional investors in monitoring is negligible.…”
Section: Impact Of Institutional Ownership On Bank Performancementioning
confidence: 78%
“…By using frontier based non-parametric technique, Data Envelopment Analysis (DEA), provides significant insights on efficiency of different banks and places private sector ones at an advantage situation and thereby hints out the possibility of further improvisation of most of the public sector banks. Rahman and Rejab (2015) suggested that the bank performance varies with different types of ownership structure. Ozili and Uadiale (2017) investigated whether ownership concentration influence banking profitability in a developing country context.…”
Section: Empirical Literaturementioning
confidence: 99%